Self-control for maintaining healthy lifestyle behaviors associated with serum lipid levels in preadolescent children in Japan: a cross-sectional study - Yamashita, Kotomi; Kawasaki, Hiromi; Yamasaki, Satoko; Nakaoka, Sae; Menuta, Bethel Fekede (Frontiers in Public Health, 2025)
IntroductionSerum lipid levels influence long-term health outcomes in children and self-control is crucial for healthy behavioral habits. This study focused on preadolescent children aged 9–10 years, who are developing self-control. Moreover, the study aimed to examine the relationship between serum lipid levels and self-control of lifestyle behavior to identify the behaviors that warrant prioritization for self-control.MethodsThe study included 545 children. Non-high-density lipoprotein cholesterol (non-HDL-C) is an indicator of current and future health status in children. Differences in non-HDL-C values were tested based on the self-control status of healthy behaviors. Given that behavioral performance is interrelated, logistic regression analysis was performed.ResultsNon-HDL-C levels were lower in groups that frequently consumed fried food and in those with poor physical condition and mood on Mondays. In logistic regression, lower serum lipid levels were associated with sufficient exercise time, poor physical condition, and mood on Mondays, lower body weight, and being male. Avoiding snacking while watching television may also be associated with lower non-HDL-C levels.DiscussionSelf-control of sufficient exercise time and adherence to snacking rules are pivotal for self-control among preadolescent children, and enhancing self-control in these behaviors can be critical in educational and intervention strategies aimed at improving health outcomes.